Growth of garment industry in Bangladesh : economic and social dimensions : proceedings of a National Seminar on Ready-made Garment Industry, held in Dhaka, Bangladesh, January 21-22, 2000 - National Seminar on Ready-made Garment Industry (2000 : Dhaka, Bangladesh); Paul-Majumder, Pratima; Sen, Binayak; Bangladesh Institute of Development Studies (Dhaka : Bangladesh Institute of Development Studies, 2001)
Seminar organized by Bangladesh Institute of Development Studies with assistance from Oxfam GB.
Includes bibliographical references.
ESS
Complimentary copy from Professor Dr. Nasreen Khundker
Keywords: Clothing trade -- Bangladesh -- Congresses; Clothing workers -- Bangladesh -- Congresses